Huge poor-rich inequalities in maternity care: an international comparative study of maternity and child care in developing countries - Tanja AJ Houweling; Carine Ronsmans; Oona MR Campbell; Anton E Kunst (The World Health Organization, 2007)
OBJECTIVE: Progress towards the Millennium Development Goals for maternal health has been slow, and accelerated progress in scaling up professional delivery care is needed. This paper describes poor-rich inequalities in the use of maternity care and seeks to understand these inequalities through comparisons with other types of health care. METHODS: Demographic and Health Survey (DHS) data from 45 developing countries were used to describe poor-rich inequalities by wealth quintiles in maternity care (professional delivery care and antenatal care), full childhood immunization coverage and medical treatment for diarrhoea and acute respiratory infections (ARI). FINDINGS: Poor-rich inequalities in maternity care in general, and professional delivery care in particular, are much greater than those in immunization coverage or treatment for childhood illnesses. Public-sector inequalities make up a major part of the poor-rich inequalities in professional delivery attendance. Even delivery care provided by nurses and midwives favours the rich in most countries. Although poor-rich inequalities within both rural and urban areas are large, most births without professional delivery care occur among the rural poor. CONCLUSION: Poor-rich inequalities in professional delivery care are much larger than those in the other forms of care. Reducing poor-rich inequalities in professional delivery care is essential to achieving the MDGs for maternal health. The greatest improvements in professional delivery care can be made by increasing coverage among the rural poor. Problems with availability, accessibility and affordability, as well as the nature of the services and demand factors, appear to contribute to the larger poor-rich inequalities in delivery care. A concerted effort of equity-oriented policy and research is needed to address the huge poor-rich inequalities in maternity care.